If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 6 + -4x + 2 + -2x Reorder the terms: 2x = 6 + 2 + -4x + -2x Combine like terms: 6 + 2 = 8 2x = 8 + -4x + -2x Combine like terms: -4x + -2x = -6x 2x = 8 + -6x Solving 2x = 8 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 2x + 6x = 8 + -6x + 6x Combine like terms: 2x + 6x = 8x 8x = 8 + -6x + 6x Combine like terms: -6x + 6x = 0 8x = 8 + 0 8x = 8 Divide each side by '8'. x = 1 Simplifying x = 1
| y=-2E+05ln(x)+1E+06 | | -6--2x/-4 | | 0x+1y=3 | | x=3y^3+4y | | 4.5(r+1)=27-4.5 | | 3m+2n=2 | | Y=-0.5x-3 | | Cos(x+50)=-0.7 | | 3n+8-4n=-17 | | 2x-6x=1-3 | | 13x+29=-10+39x | | x^2+y^2+6xy+10=0 | | k-11=60 | | z/2−6≤−2 | | (3+1)(2x-5)= | | (2x+4)(x-6)= | | x-2=-27 | | -22=6(2(-5.33)+7) | | 3x+8y-6z=24 | | 2x=20+20 | | k/-3-11 | | -5n+8=-07 | | 6(2(5.33)+7)= | | F(x)=7x^3 | | 4(2x-5)=120 | | -49x^2=-64 | | y=0.0002x^3-0.04x^2+2x | | 4x-26=3x | | 2w+1l= | | -22=6(2k+7) | | 50-80+30=-60 | | n^2-n-93=0 |